Etching Composition
Patent Information
- Application Number
- JP2024569040
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-11-13
- Filing Date
- 2024-07-25
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2044-07-25
AI Technical Summary
【0010】 本開示により、ケイ酸塩を必須とすることなく、なおかつ、少量の添加剤含有量であっても、従来のシラン系エッチング組成物と比べ、シリコン酸化膜に対するシリコン窒化膜のエッチング選択比が高いエッチング組成物、及びその製造方法の少なくともいずれか、を提供することができる。
Smart Images

Figure 0007632780000001 
Figure 0007632780000002 
Figure 0007632780000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to etching compositions, and more particularly to etching compositions suitable for selectively etching silicon nitride films. [Background technology]
[0002] NAND type flash memory is manufactured by a manufacturing method having an etching process for selectively removing only silicon nitride film from a substrate in which silicon oxide films such as silicon dioxide (SiO2) films and silicon nitride films such as silicon nitride (Si3N4) films are alternately laminated. To achieve higher speed and larger capacity, the circuit structure of NAND type flash memory has changed from a planar type to a 3D type and has become finer. To manufacture NAND type flash memory with a fine structure, an etching composition that can more selectively etch and remove the silicon nitride film is required in the etching process, and in particular, a phosphoric acid-based etching composition containing a silane compound as an additive has been investigated.
[0003] For example, Patent Document 1 discloses an etching composition for silicon nitride containing a silane coupling agent and water. The etching composition is said to exhibit high selectivity for silicon nitride films, with the etching rate of silicon nitride films being 1000 or more relative to the etching rate of silicon oxide films, due to the inclusion of inorganic silicate. In addition, Non-Patent Document 1 reports a phosphoric acid-based etching composition containing allylmethoxysilane as an additive. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2020-145343 [Non-patent literature]
[0005] [Non-Patent Document 1] Applied Surface Science, Volume 608, 155143 (2023) Summary of the Invention [Problem to be solved by the invention]
[0006] In Patent Document 1, the etching selectivity is increased by adding silicate. However, etching compositions containing silicate are contaminated with counter cations, especially metal counter cations such as sodium, after etching. On the other hand, the etching composition disclosed in Non-Patent Document 1 does not have sufficient selectivity, with an etching selectivity ratio of only about 120 to 280 even when the content of the additive is relatively high at 0.1 M (0.95 mass%).
[0007] The present disclosure aims to provide at least one of an etching composition that does not require a silicate and has a high etching selectivity for a silicon nitride film relative to a silicon oxide film, compared with conventional silane-based etching compositions, even when the additive content is small, and a method for producing the same. [Means for solving the problem]
[0008] In this disclosure, a phosphoric acid-based etching composition containing a silane compound was investigated. As a result, it was found that a phosphoric acid-based etching composition containing a specific silane compound as an additive exhibits excellent etching selectivity even with a small amount of additive, and in particular, exhibits an etching selectivity equal to or higher than that of allyltrimethoxysilane disclosed in Non-Patent Document 1.
[0009] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] An etching composition containing phosphoric acid, allyltrimethoxysilane, a decomposition product of allyltrimethoxysilane, and a solvent. [2] The etching composition according to [1] above, wherein the content of the allyltrimethoxysilane is 0.005% by mass or more and 10% by mass or less. [3] The etching composition according to [1] or [2] above, wherein the content of the allyltrimethoxysilane is 0.02 mass % or more and 0.5 mass % or less. [4] The etching composition according to any one of [1] to [3] above, wherein the concentration of the phosphoric acid is 60% by mass or more and 95% by mass or less. [5] The etching composition according to any one of [1] to [4] above, wherein the solvent comprises water. [6] The etching composition according to any one of [1] to [5] above, wherein the solvent is a water-alcohol mixed solvent. [7] The decomposition product of the allyltrimethoxysilane has the general formula (CH2=CHCH2)Si(OH) n (OMet) 3-n (wherein Met is a methyl group, and n is an integer of 1 to 3). [8] A method for producing the etching composition according to any one of [1] to [7] above, comprising heat-treating an aqueous solution containing allyltrimethoxysilane and phosphoric acid at a temperature of 80°C or higher and lower than 160°C. [9] A method for etching a silicon nitride film, which uses the etching composition according to any one of [1] to [7] above.
[10] A method for manufacturing a semiconductor memory, comprising etching using the etching composition according to any one of [1] to [7] above. Effect of the Invention
[0010] According to the present disclosure, it is possible to provide at least one of an etching composition that does not require silicate and has a high etching selectivity for a silicon nitride film relative to a silicon oxide film, compared with conventional silane-based etching compositions, even with a small amount of additives contained therein, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present disclosure will be described with reference to an example of an embodiment. The terms used in this embodiment are as follows. The configurations and parameters disclosed in this specification may be combined in any combination, and the upper and lower limits of the values disclosed in this specification may be combined in any combination.
[0012] [Etching composition] The present embodiment is an etching composition containing phosphoric acid, allyltrimethoxysilane, a decomposition product of allyltrimethoxysilane, and a solvent. The etching composition of the present embodiment can be used for selective etching of a silicon nitride film, particularly for selective etching of a silicon nitride film from a substrate having a silicon oxide film and a silicon nitride film.
[0013] (phosphoric acid) The etching composition of the present embodiment contains phosphoric acid, which promotes etching of the silicon nitride film.
[0014] The phosphoric acid contained in the etching composition of the present embodiment is orthophosphoric acid (H3PO4), pyrophosphoric acid (H4P2O7), metaphosphoric acid (HPO3), n (n is a positive integer), and polyphosphoric acid (HO(HPO3) n H) (n is a positive integer).
[0015] The content of phosphoric acid in the etching composition of the present embodiment is, as a mass ratio of phosphoric acid to the mass of the etching composition, 60 mass% or more, or 80 mass% or more, and 95 mass% or less, or 90 mass% or less. In addition, this mass ratio is preferably 60 mass% or more and 95 mass% or less, or 80 mass% or more and 90 mass% or less.
[0016] The content of phosphoric acid in the etching composition of the present embodiment is the mass ratio of phosphoric acid to the mass of the etching composition.
[0017] (Allyltrimethoxysilane) The etching composition of the present embodiment contains allyltrimethoxysilane. Allyltrimethoxysilane is included as a silane compound additive. As a result, the etching composition of the present embodiment exhibits a high etching selectivity.
[0018] Furthermore, the etching composition of this embodiment contains allyltrimethoxysilane as well as a decomposition product of allyltrimethoxysilane (hereinafter also referred to as a "partial decomposition product"). The partial decomposition product is a silane compound obtained by partially decomposing allyltrimethoxysilane by hydrolysis or the like, and is considered to have a higher film-forming ability, i.e., a higher protective layer-forming ability, on a silicon oxide film than allyltrimethoxysilane. Therefore, by containing the partial decomposition product, etching of the silicon oxide film is further suppressed. In addition, the partial decomposition product is considered to be preferable for suppressing precipitates derived from allyltrimethoxysilane.
[0019] The partial decomposition product has the general formula (CH2=CHCH2)Si(OH) n (OMet) 3-n (wherein Met is a methyl group, and n is an integer of 1 to 3).
[0020] The content of allyltrimethoxysilane, expressed as the mass ratio of allyltrimethoxysilane to the mass of the etching composition, is, for example, 0.005 mass% or more, 0.01 mass% or more, 0.02 mass% or more, 0.05 mass% or more, or 0.1 mass% or more, and also 10 mass% or less, 5 mass% or less, 3 mass% or less, 1 mass% or less, 0.8 mass% or less, 0.5 mass% or less, 0.3 mass% or less, 0.25 mass% or less, 0.2 mass% or less, or 0.175 mass% or less. The content of allyltrimethoxysilane is 0.005 mass% or more and 10 mass% or less, 0.005 mass% or more and 3 mass% or less, 0.005 mass% or more and 0.8 mass% or less, 0.01 mass% or more and 0.8 mass% or less, 0.01 mass% or more and 0.5 mass% or less, 0.02 mass% or more and 0.5 mass% or less, 0.02 mass% or more and 0.3 mass% or less. 0.02 mass% or more and 0.25 mass% or less, 0.02 mass% or more and 0.175 mass% or less, 0.05 mass% or more and 0.5 mass% or less, 0.05 mass% or more and 0.3 mass% or less, 0.05 mass% or more and 0.2 mass% or less, 0.05 mass% or more and 0.175 mass% or less, or 0.1 mass% or more and 0.3 mass% or less. When the content of allyltrimethoxysilane satisfies this range, the etching selectivity is likely to be high, and precipitates derived from allyltrimethoxysilane can be suppressed. By suppressing the precipitates, the etching composition of this embodiment can be applied to etching of laminated substrates having finer structures. In addition, the etching selectivity does not increase as the content of allyltrimethoxysilane increases, and in order to obtain a high etching selectivity, the content of allyltrimethoxysilane is preferably 0.3 mass% or less, 0.25 mass% or less, 0.2 mass% or less, or 0.175 mass% or less. In the etching composition of this embodiment, for convenience, the total content of the partial decomposition product and allyltrimethoxysilane may be regarded as the content of allyltrimethoxysilane.
[0021] (solvent) The etching composition of this embodiment contains a solvent. The solvent may be at least one of water and alcohol, and may further be water. The water may be one or more selected from the group consisting of ion-exchanged water, distilled water, pure water, and ultrapure water. In addition, when the raw materials of phosphoric acid and allyltrimethoxysilane are in the form of a solution, the solvent of this solution can function as the solvent of the etching composition of this embodiment. The solvent is preferably water and alcohol, more preferably water and methanol, or further preferably a water-alcohol mixed solvent. The solvent is particularly preferably water and methanol produced by hydrolysis of allyltrimethoxysilane.
[0022] (Other Ingredients) The etching composition of the present embodiment may contain additives other than allyltrimethoxysilane, for example, at least one of a silicon compound other than allyltrimethoxysilane and a fluorine compound, as long as the effect of the composition is not impaired.
[0023] As described above, the etching composition of this embodiment does not necessarily include silicate. Therefore, the etching composition of this embodiment can reduce the concentration of counter cations, particularly metal counter cations such as sodium. For example, the etching composition of this embodiment may have a metal ion concentration of 1.00 mass% or less, 0.50 mass% or less, 0.10 mass% or less, 0.05 mass% or less, 0.01 mass% or less, 0.005 mass% or less, 0.001 mass% or less, 0.0005 mass% or less, or 0.0001 mass% or less (1 ppm). The lower limit of the metal ion concentration may be more than 0 mass% and 0.00001 mass% or more.
[0024] (Composition (content)) The composition (content) of the etching composition of this embodiment can be measured by a known method. For example, the phosphoric acid content can be measured by molybdenum blue absorptiometry, the water content can be measured by a Karl Fischer moisture meter, and the allyltrimethoxysilane content can be measured by nuclear magnetic resonance analysis. The metal ion concentration can be measured by ICP-MASS.
[0025] [Method of manufacturing the etching composition] A preferred method for producing the etching composition of this embodiment includes a production method including heat-treating an aqueous solution containing allyltrimethoxysilane and phosphoric acid at 80° C. or more and less than 160° C. (hereinafter, also referred to as a "heat treatment step"). This heat treatment partially decomposes allyltrimethoxysilane to generate a partial decomposition product. The partial decomposition product is considered to have a high ability to form a protective layer for the silicon oxide film, and thus exhibits a high etching selectivity. In addition, methanol is generated together with the partial decomposition product, and the solvent becomes a mixed solvent of water and alcohol. In this embodiment, the "aqueous solution" means a solution in which the solvent contains at least water, particularly a solution in which 1% by mass or more, 3% by mass or more, 5% by mass or more, 10% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more of the solvent is water. The upper limit of the water content in the aqueous solution can be 99% by mass or less, 98% by mass or less, or 95% by mass or less. The water content in the aqueous solution can be, for example, from 1% by mass to 99% by mass, from 10% by mass to 98% by mass, or from 50% by mass to 95% by mass.
[0026] The aqueous solution containing allyltrimethoxysilane and phosphoric acid (hereinafter also referred to as "raw aqueous solution") to be subjected to the heat treatment step may contain phosphoric acid and allyltrimethoxysilane, and may further contain water as a solvent. The raw aqueous solution is preferably in a state obtained by mixing an aqueous phosphoric acid solution with allyltrimethoxysilane, and more preferably in a state obtained by adding allyltrimethoxysilane to an aqueous phosphoric acid solution.
[0027] The content of phosphoric acid in the raw aqueous solution is, for example, 60% by mass or more, or 80% by mass or more, and 95% by mass or less, or 90% by mass or less. This content is preferably 60% by mass or more and 95% by mass or less, or 80% by mass or more and 90% by mass or less.
[0028] The content of allyltrimethoxysilane in the raw material aqueous solution is preferably 0.005% by mass or more, 0.01% by mass or more, 0.02% by mass or more, 0.05% by mass or more, or 0.1% by mass or more, and 10% by mass or less, 5% by mass or less, 3% by mass or less, 1% by mass or less, 0.8% by mass or less, 0.5% by mass or less, 0.3% by mass or less, 0.25% by mass or less, 0.2% by mass or less, or 0.175% by mass or less. In addition, this content is 0.005 mass% or more and 10 mass% or less, 0.005 mass% or more and 3 mass% or less, 0.005 mass% or more and 0.8 mass% or less, 0.01 mass% or more and 0.8 mass% or less, 0.01 mass% or more and 0.5 mass% or less, 0.02 mass% or more and 0.5 mass% or less, 0.02 mass% or more and 0.3 mass% or less, 0.0 It is preferable that the content is 2% by mass or more and 0.25% by mass or less, 0.02% by mass or more and 0.175% by mass or less, 0.05% by mass or more and 0.5% by mass or less, 0.05% by mass or more and 0.3% by mass or less, 0.05% by mass or more and 0.2% by mass or less, 0.05% by mass or more and 0.175% by mass or less, or 0.1% by mass or more and 0.3% by mass or less.
[0029] In the heat treatment step, for example, the raw material aqueous solution is heat treated at 80°C or higher and lower than 160°C. This is believed to cause local decomposition of allyltrimethoxysilane. As a result, methanol is generated and allyltrimethoxysilane is more likely to form a protective layer on the silicon oxide film. The heat treatment is preferably performed in a sealed state. On the other hand, at 160°C or higher, the decomposition of allyltrimethoxysilane proceeds excessively, inhibiting the generation of partial decomposition products and decreasing the etching selectivity. The following conditions are preferred as heat treatment conditions. Heat treatment atmosphere: oxidizing atmosphere or inert atmosphere, preferably air atmosphere Heat treatment temperature: 80°C or higher, 100°C or higher, 110°C or higher, 115°C or higher, or 120°C or higher, and less than 160°C, 155°C or lower, 150°C or lower, 140°C or lower, or 130°C or lower (for example, 80°C or higher and less than 160°C, 100°C or higher and 155°C or lower, 110°C or higher and 150°C or lower, 115°C or higher and 140°C or lower, or 120°C or higher and 130°C or lower) Heat treatment pressure: Autogenous pressure
[0030] The heat treatment time may be appropriately adjusted depending on the amount of the etching composition to be produced and the scale of the production apparatus, and may be, for example, 5 minutes or more, or 7 minutes or more, and may be 120 hours or less, 30 minutes or less, or 15 minutes or less. In addition, examples of the heat treatment time include 5 minutes or more and 120 hours or less, 5 minutes or more and 30 minutes or less, or 7 minutes or more and 15 minutes or less.
[0031] [Etching method] The etching composition of the present embodiment can be used for etching a silicon nitride film, particularly for selective etching of a silicon nitride film on a substrate having a silicon oxide film and a silicon nitride film. The etching of a silicon nitride film using the etching composition of the present embodiment may be performed by an etching method including contacting the etching composition of the present embodiment with a substrate having a silicon nitride film, particularly a substrate having a silicon oxide film and a silicon nitride film (hereinafter also referred to as an "etching step").
[0032] The etching step provides a substrate having a silicon nitride film. The substrate may be any substrate used as a semiconductor, further a semiconductor used in a NAND memory, and may be one or more substrates selected from the group consisting of a silicon substrate, a SiC substrate, a sapphire substrate, and a glass substrate, and is preferably a silicon substrate.
[0033] The substrate has a silicon nitride film on its surface, which may be formed by at least one method selected from the group consisting of low pressure chemical vapor deposition (LPCVD), plasma enhanced chemical vapor deposition (PECVD) and atomic layer deposition (ALD).
[0034] The substrate may have a silicon oxide film in addition to the silicon nitride film (hereinafter, a substrate having at least one of a silicon nitride film and a silicon oxide film is also referred to as a "film-coated substrate"). The method for forming the silicon oxide film is arbitrary, but examples of the silicon oxide film include silicon oxide films formed by one or more methods selected from the group consisting of thermal oxidation, low pressure chemical vapor deposition (LPCVD), plasma enhanced chemical vapor deposition (PECVD) and atomic layer deposition (ALD), and silicon oxide films formed by at least one of PECVD and thermal oxidation.
[0035] The substrate may be a substrate having a silicon nitride film and a silicon oxide film, in particular a substrate having a laminated film in which a silicon nitride film and a silicon oxide film are laminated.
[0036] In the etching step, the etching composition of the present embodiment is brought into contact with a substrate having a silicon nitride film. This etches the silicon nitride film. The method of bringing the etching composition into contact with the substrate is arbitrary, and examples thereof include immersing the substrate having a silicon nitride film in the etching composition of the present embodiment, passing the etching composition of the present embodiment over the substrate having a silicon nitride film, and spraying the etching composition of the present embodiment over the substrate having a silicon nitride film.
[0037] The temperature of the contact may be any temperature at which etching with phosphoric acid proceeds, and may be, for example, 100° C. or more, 120° C. or more, 140° C. or more, or 150° C. or more, and may be 200° C. or less, 180° C. or less, 170° C. or less, or 160° C. or less. The temperature is, for example, 100° C. or more and 200° C. or less, or 120° C. or more and 180° C. or less, and is preferably 140° C. or more and 170° C. or less, or 150° C. or more and 160° C. or less.
[0038] The contact time may be adjusted appropriately depending on the size of the substrate to be subjected to the etching process, the shape of the silicon nitride film, and the desired etching degree, and the longer the contact time, the more the etching progresses. The contact time may be, for example, 1 minute or more, or 5 minutes or more, and may be 1440 minutes or less, or 240 minutes or less. The time may be, for example, 1 minute or more and 1440 minutes or less, or 5 minutes or more and 240 minutes or less.
[0039] The etching composition of the present embodiment can be applied to a method for manufacturing a semiconductor memory, which includes etching using the etching composition, and further, the etching composition of the present embodiment can be applied to a method for manufacturing a semiconductor memory having a 3D structure, which includes etching using the etching composition. EXAMPLES
[0040] The present disclosure will be described in detail below with reference to examples. However, the present disclosure is not limited to these examples.
[0041] (film thickness measurement) Using a diamond cutter, silicon substrates with silicon nitride film or silicon oxide film (hereinafter also referred to as "film-coated substrates") were cut into 10 mm x 10 mm square plates to prepare measurement samples. Using a microspectrophotometer (device name: OPTM-F1, manufactured by Otsuka Electronics Co., Ltd.), the film thickness of the film-coated wafers was measured under the following conditions. Measurements were performed at five points per sample, and the average value was taken as the film thickness of the measurement sample. Number of times: 20 Exposure time: 100msec Wavelength range: 230~800nm
[0042] Examples 1 to 10 Allyltrimethoxysilane (product name: Allyltrimethoxysilane, manufactured by Tokyo Chemical Industry Co., Ltd.) was weighed and filled into a 100 mL plastic container so as to obtain the composition shown in Table 1 below, and then 85% phosphoric acid aqueous solution (product name: EL-S, manufactured by Rinkagaku Kogyo Co., Ltd.) was gradually added to obtain a mixed aqueous solution. After stirring, the obtained mixed aqueous solution was heated in the plastic container at 120°C in the air for 10 minutes to obtain the etching composition of this example.
[0043] Comparative Example 1 An etching composition of this comparative example was obtained in the same manner as in Example 8, except that 0.500 g of n-octyltrimethoxysilane was used instead of 0.500 g of allyltrimethoxysilane.
[0044] Comparative Example 2 An etching composition of this comparative example was obtained in the same manner as in Example 8, except that 0.500 g of hexadecyltriethoxysilane was used instead of 0.500 g of allyltrimethoxysilane.
[0045] Comparative Example 3 An etching composition of this comparative example was obtained in the same manner as in Example 2, except that the heat treatment in the air at 120° C. for 10 minutes was not performed.
[0046] The etching compositions of the Examples and Comparative Examples obtained as described above did not substantially contain metal ions.
[0047] [Etching process] A silicon substrate with a silicon nitride film having a silicon nitride film formed by a PECVD method and a silicon substrate with a silicon oxide film having a silicon oxide film formed by a PECVD method were immersed in the etching compositions of Examples 1 to 9 and Comparative Examples 1 to 3, respectively, and etched by heating at 157°C. The etching time for the silicon substrate with a silicon nitride film was 5 minutes. On the other hand, the silicon oxide film was not etched at all when the etching time was 10 minutes. Therefore, the etching time for the silicon substrate with a silicon oxide film was 240 minutes.
[0048] After the etching treatment, the film thickness was measured for the film-coated substrate after washing with pure water and air drying, and for the film-coated substrate before the etching treatment. From the results, the etching rate and the etching selectivity were calculated according to the following formulas.
[0049] ER = (T BF -T AF ) / E t (1) In the above formula, ER is the etching rate [nm / min], T AF is the thickness after etching [nm], T BF is the film thickness before etching [nm], and E t is the etching process time [min].
[0050] ES = ER SiN / ER SiO2 (2) In the above formula, ES is the etching selectivity, ER SiN is the etching rate of silicon nitride film [nm / min], and ER SiO2 is the etching rate of the silicon oxide film [nm / min]. The results are shown in Table 1.
[0051] [Table 1]
[0052] From the above table, it was confirmed that, up to a certain level of allyltrimethoxysilane content, the etching selectivity tends to increase as the allyltrimethoxysilane content increases, and in particular, when the allyltrimethoxysilane content is 0.175 mass% or more, a very high etching selectivity is shown. Furthermore, it was confirmed that the etching selectivity in the etching composition of Example 2, in which the allyltrimethoxysilane content is 0.025 mass%, is 234, and that the selectivity is the same as the etching selectivity disclosed in Non-Patent Document 1. On the other hand, since the etching selectivity of Example 7, in which the allyltrimethoxysilane content is 0.175 mass%, is higher than that of Examples 8 and 9, in which the allyltrimethoxysilane content is 0.500 mass% and 2.500 mass%, respectively, it was confirmed that there is an appropriate range for the allyltrimethoxysilane content in order to obtain a high etching selectivity.
[0053] From a comparison between Comparative Example 1 and Comparative Example 2, it was confirmed that the shorter the alkyl chain of the silane compound, the higher the etching selectivity. Furthermore, it was confirmed that, although the silane compounds of Comparative Example 1 and Example 8 have the same alkyl chain and the same amount of silane compound, the etching selectivity of Example 8 (13,000) is significantly larger (100 times or more) than the etching selectivity of Comparative Example 1 (113). Furthermore, it was confirmed that Example 5, which has an additive content (0.100 mass%) of about 1 / 10 of the additive concentration (0.1 M) disclosed in Non-Patent Document 1, has an etching selectivity of 1700, which is extremely higher than the etching composition of Non-Patent Document 1.
[0054] [Table 2]
[0055] From Table 2, it was confirmed that the etching composition that was not heat-treated had a lower etching selectivity than the etching composition that was heat-treated, by comparing Example 2, which was heat-treated in an air atmosphere at 120°C for 10 minutes, with Comparative Example 3, which was not heat-treated. From this, it was confirmed that the decomposition products of allyltrimethoxysilane generated by the heat treatment exist, and this improves the etching selectivity.
[0056] In addition, the etching composition of Example 7 was used to etch a silicon substrate having a silicon oxide film formed by a thermal oxidation method in addition to the etching of a silicon substrate having a silicon oxide film formed by a PECVD method. The results are shown in Table 3 below.
[0057] [Table 3]
[0058] From the above table, it was confirmed that the etching selectivity when using the silicon oxide film formed by the thermal oxidation method was about the same as that when using the silicon oxide film formed by the PECVD method. This confirmed that the etching composition of this embodiment can perform etching with a high etching selectivity regardless of the method of forming the silicon oxide film.
Claims
1. The method includes heat treating an aqueous solution containing allyltrimethoxysilane and phosphoric acid at a temperature of 80° C. or higher and lower than 160° C. A method for producing an etching composition, the etching composition containing phosphoric acid, allyltrimethoxysilane, a decomposition product of allyltrimethoxysilane, and a solvent.
2. The manufacturing method described in claim 1, wherein the content of allyltrimethoxysilane in the aqueous solution is 0.005 mass% or more and 10 mass% or less.
3. A manufacturing method described in claim 1 or 2, wherein the phosphoric acid content in the aqueous solution is 60 mass% or more and 95 mass% or less.
4. A manufacturing method described in claim 1 or 2, wherein the heat treatment temperature in the heat treatment is 110°C or higher and 150°C or lower.
5. A manufacturing method described in claim 1 or 2, wherein the heat treatment time in the heat treatment is 5 minutes or more and 120 hours or less.
6. A manufacturing method described in claim 1 or 2, wherein the heat treatment atmosphere in the heat treatment is an air atmosphere.
Citation Information
Patent Citations
Silicon nitride film etching solution and production method thereof
JP2021015968A
Etching composition for silicon nitride layer and etching method using the same
KR102325905B1
Silanol based dental treatment
US20070009448A1
Silicon nitride etchant composition
JP2020145343A